Interleukin-6: A Novel Target for Cardio-Cerebrovascular Diseases - Jian-Hui Su; Jian-Hui Su; Meng-Yi Luo; Meng-Yi Luo; Na- Liang; Shao-Xin Gong; Wei Chen; Wei Chen; Wen-Qian Huang; Wen-Qian Huang; Ying Tian; Ai-Ping Wang; et al. (Frontiers Media S.A., 2021)
Cardio-Cerebrovascular Disease is a collective term for cardiovascular disease and cerebrovascular disease, being a serious threat to human health. A growing number of studies have proved that the content of inflammatory factors or mediators determines the stability of vascular plaque and the incidence of cardio-cerebrovascular event, and involves in the process of Cardio-Cerebrovascular Diseases. Interleukin-6 is a widely used cytokine that causes inflammation and oxidative stress, which would further result in cardiac and cerebral injury. The increased expression of interleukin-6 is closely related to atherosclerosis, myocardial infarction, heart failure and ischemic stroke. It is a key risk factor for these diseases by triggering inflammatory reaction and inducing other molecules release. Therefore, interleukin-6 may become a potential target for Cardio-Cerebrovascular Diseases in the future. This paper is aimed to discuss the expression changes and pathological mechanisms of interleukin-6 in Cardio-Cerebrovascular Diseases, and to provide a novel strategy for the prevention and treatment of Cardio-Cerebrovascular Diseases.